NcRNA-mediated upregulation of CAMK2N1 is associated with poor prognosis and tumor immune infiltration of gastric cancer - Peng, Kaipeng; Ren, Xiangqing; Ren, Qian (Frontiers in Genetics, 2022)
Gastric cancer (GC) is still notorious for its poor prognosis and aggressive characteristic. Though great developments have been made in diagnosis and therapy for GC, the prognosis of patients’ is still perishing. In this study, differentially expressed genes (DEGs) in GC were first screened using 3 Gene Expression Omnibus (GEO) datasets (GSE13911, GSE29998, GSE26899). Secondly, The Cancer Genome Atlas (TCGA) and The Genotype-Tissue Expression (GTEx) data was used to validate expression of these DEGs and perform survival analysis. We selected 7 candidate genes (CAMK2N1, OLFML2B, AKR7A3, CYP4X1, FMO5, MT1H, MT1X) to carry out next analysis. To construct ceRNA network, we screened most potential upstream ncRNAs of the candidate genes. By a series of bioinformatics analyses including expression analysis, correlation analysis, and survival analysis, the SNHG10-hsa-miR-378a-3p might be the most potential regulatory axis in GC. Then, the expression of the CAMK2N1, miR-378a-3p and SNHG10 were verified in GC cell lines (GES-1, MGC-803, BGC-823, HGC-27, MKN-45, AGS) by RT-qPCR and western blot. We found that SNHG10 and CAMK2N1 were highly expressed in gastric cancer lines, and the miR-378a-3p was lowly expressed in BGC-823, HGC-27, MKN-45. Furthermore, CAMK2N1 level was significantly negatively associated with tumor immune cell infiltration, biomarkers of immune cells, and immune checkpoint expression. In sum, our results suggest that ncRNA-mediated high expression of CAMK2N1 is associated with poor prognosis and tumor immune infiltration of GC